ADSORPTION OF HEAVY METALS USING ACTIVATED CARBONS PREPARED FROM AGUAJE STONES - Sun-Kou, María del Rosario (2014)
Aguaje seed (a typical Amazonian forest fruit) was used as a precursor material for the production of activated carbon using phosphoric acid as activating agent in two different concentrations: 0,75 and 1,0 gH3PO4/gPrecursor. The physicochemical properties were studied by N2 sorption measurements, Boehm titration, scanning electron microscopy and energydispersive X-ray spectroscopy. Activated carbons were used in the adsorption of three heavy metals: lead, cadmium and chromium. The maximum adsorption capacity was achieved using activated carbon AG0,75_600 in a solution with a pH greater than 4 and the values -1 -1 obtained were in the following order: lead (74,8 mg g ), cadmium (26,5 mg g ), chromium -1 (18,8 mg g ). The most important factors influencing the adsorption process were the pH of the solution, the porous structure and surface acidity of the activated carbon.